Institutional logics and social mechanisms: a pragmatic multilevel perspective - Costa, Mayla Cristina; Teixeira, Maísa Gomide (Revista de Administração da UFSM, 2013)
DOI: 10.5902/198346598220 Institutionalists have argued about some different toolkit for addressing the paths of historical change in the different areas of research, including the development of a set of social mechanisms that may help to account for the impact of macro-level changes on the micro or individual level. In recent years institutional research has been focusing on institutional logics as an analytical approach with a higher potential to solve this puzzle. Therefore the main goal of this paper is to open a research stream onto a focus on a methodological approach and analytical tool to study multi-level relationships. For instance, a topic that has been claimed as still in need of more consideration, the understanding of how organizations are influenced by competing logics, and the implications of those logics in terms of practices performed by actors and group identity formation, could be better explored.